Prácticas de enseñanza de matemática en tercer año de Educación General Básica de la Unidad Educativa Santa Dorotea de Quito. - Vargas Jaramillo, Adriana Elizabeth (2016)
Talking about pedagogical practicing is talking about a social practicing influenced by many facts which includes from the proper formation of the teacher to the particularities of his context in where this process is developed. For this reason, the present investigative work has as purpose to analyze the practicing in the subject of Mathematics in the third year of Basic General Education in the high school “Santa Dorotea” using the ethnographic method and the qualitative approaches to describe and contrast what the teachers said versus what they do about the form of planning, the methodology, evaluation process, and the form that the process of learning-teaching in the classroom is organized, as well as the interactions that happen between teachers and students in the subject already mentioned. For this purpose, the analysis of the various theoretical conceptualizations of teaching practice , the behavior of the process of learning of Mathematics from the Ecuadorian curriculum concerning the analysis of the various methodological strategies , talk about the teaching resources area is performed, finally it considered an analytical treatment of the implementation of the evaluation of learning. It was concluded that teachers involved in the investigation try to develop a constructivist-critic approach in the process, but they still are influenced by features of the traditional model of teaching Mathematics.